HnRNP L is essential for peripheral T cell proliferation and survival - White, Tristan L. A.; Henry, Devin J.; Roberts, Sean D. A.; Jin, Ye; Gong, Yi-Nan; Morel, Penelope A. (Frontiers in Immunology, 2025)
IntroductionDuring T cell development, heterogeneous nuclear ribonucleoprotein (hnRNP) L is known to regulate CD4 T helper subset differentiation, the proliferation and migration of thymocytes, as loss of hnRNP L in early T cell development results in a failure of T cells to reach the periphery. MethodsTo better understand the role of hnRNP L in modulating peripheral T cell trafficking and function, we analyzed T survival and activation in newly generated CD4Cre x hnRNP LFl/Fl (KO) mice. In vitro and in vivo analyses of CD4 T cell differentiation, T cell proliferation and death post activation were performed.ResultsOur initial study of the steady state profile of the KO mice showed normal migration of T cells from the thymus, but peripheral T cell numbers were reduced. Analysis of TCR-mediated signaling pathways revealed normal early T cell activation. However, T cells lacking hnRNP L had marked defects in their ability to differentiate into T helper cell subsets due to reduced proliferation and increased death. In vivo, using immunization studies, KO CD4 T cells failed to fully differentiate into T follicular helper (Tfh) cells and were unable to support the formation of germinal center B cells. Death of activated hnRNP L KO cells could be reversed by treating the cells with zVAD, a pan-caspase inhibitor. In addition, hnRNP L KO cells failed to upregulate the anti-apoptotic protein Bcl-XL following activation. DiscussionThese studies suggest that hnRNP L plays an important role in T cell activation and survival. Our studies suggest that hnRNP L plays a critical pro-survival role in activated T cells and that alternative splicing of factors that prevent apoptosis may be an important mechanism by which this is achieved.